Coronabrotica, a new genus and species of Luperini, and a key to genera of Section Phyllecthrites (Coleoptera, Chrysomelidae, Galerucinae) - de A. Moura, Luciano (Zootaxa, 2010)
Coronabrotica, a new genus of Diabroticina Section Phyllecthrites (Luperini) is proposed from the Neotropical Region with the type-species Coronabrotica amazonensis Moura sp. nov. from states of Pará and Amazonas, north of Brazil. The new genus differs from others of the Section by the anterior coxal cavities being closed and, in males, by a rounded pore on the basal half of the pronotum, surrounded by a crown of long erect setae. Descriptions and illustrations of the new taxa and a key for the identification of the thirteen genera that compose the Section Phyllecthrites are provided.